THE SURVIVAL OF TRADITIONAL MUSIC AND ITS CURRENT APPEAL IN CENTRAL THAILAND - Zamira Najla Binti Zaimi (Lakon : Jurnal Kajian Sastra dan Budaya, 2020)
Traditional music in Central Thai society is a rich piece of culture that uncovers much about day to day existence in the society. This study investigates the factors contributing to the music’s declining appeal to the local people. It focuses on  customary music in five focal regions of Thailand. In collecting the data, I combined survey, interviews, and observation. The analysis shows that the popularity and appeal of customary music in Central Thailand is declining. The decline is partly caused by the wide impacts of Western cultures and music on Thai society.  Moreover, there are not many youngsters who are keen on preserving the existence of the traditional music. This is coupled with the absence of the government in supporting the survival of the music. It is pity as the folk music is very much in tune with the everyday life of  Central Thai society. However, in order to survive it requires modernization and adaptation with the changing dynamics of the society.